(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aimed to assess how motivation, training, and professionalism impact employee performance. This study was carried out at the Ari Canti Consumer Cooperative in Ubud District, Gianyar Regency. This study included 32 cooperative employees as part of the population. The sampling was conducted utilizing the census technique. Data was gathered through interviews, reviewing literature, and distributing questionnaires. The Likert Scale, consisting of five answer choices, is the scale of measurement used for the data. Validity and reliability tests were conducted to assess the instruments. Multiple linear regression was utilized for hypothesis testing with the help of SPSS software. The findings confirm that motivation, job training, and professionalism all have a positive and significant impact on employee performance.